Quantitative studies of the Renaissance Florentine economy and society - Lindholm, Richard T. (Anthem Other Canon economics, 2017)
The book is a collection of nine quantitative studies about Renaissance Florentine economy and society. Topics include plague outbreaks, interest rates, wealth distribution, taxes and subsidies, art history, neighbourhood segregation, competitive markets and monopoly power, women's work and business risk.